Clinical differences between younger and older adults with HIV/AIDS starting antiretroviral therapy in Uganda and Zimbabwe: a secondary analysis of the DART trial - Parikh, S; Obuku, E; Walker, SA; Semeere, A; Auerbach, B; Hakim, J; Mayanja-Kizza, H; Mugyenyi, P; Salata, R; Kityo, C (Public Library of Science, 2013)
OBJECTIVE: Clinical and immunological data about HIV in older adults from low and middle income countries is scarce. We aimed to describe differences between younger and older adults with HIV starting antiretroviral therapy in two low-income African countries. METHODS: SETTING: HIV clinics in Uganda and Zimbabwe. DESIGN: Secondary exploratory cross-sectional analysis of the DART randomized controlled trial. OUTCOME MEASURES: Clinical and laboratory characteristics were compared between adults aged 18-49 years (younger) and ≥ 50 years (older), using two exploratory multivariable logistic regression models, one with HIV viral load (measured in a subset pre-ART) and one without. RESULTS: A total of 3316 eligible participants enrolled in DART were available for analysis; 219 (7%) were ≥ 50 years and 1160 (35%) were male. Across the two adjusted regression models, older adults had significantly higher systolic blood pressure, lower creatinine clearance and were consistently less likely to be females compared to younger adults with HIV. Paradoxically, the models separately suggested that older adults had statistically significant (but not clinically important) higher CD4+ cell counts and higher plasma HIV-1 viral copies at initiation. Crude associations between older age and higher baseline hemoglobin, body mass index, diastolic blood pressure and lower WHO clinical stage were not sustained in the adjusted analysis. CONCLUSIONS: Our study found clinical and immunological differences between younger and older adults, in a cohort of Africans starting antiretroviral therapy. Further investigations should explore how these differences could be used to ensure equity in service delivery and affect outcomes of antiretroviral therapy.